Antonyms, or Antagonism in Language (on the Example of Feelings of Love and Hate) - Wójcik, Magdalena Ambra (Respectus Philologicus, 2023)
The aim of the article was to show the opposition of lexemes love and hate by carrying out a pragmatic-discursive analysis of them (with a particular emphasis on the Biblical Discourse). It was concluded that from the semantic point of view, love and hate are long-lasting feelings with a strong emotional charge in opposition to each other. The expressions containing such a component as hate in various word forms have an unambiguously negative connotation while using the words love in most cases makes the message positive. The antagonism of the language units mentioned above is particularly evident in the Biblical Discourse, which is conditioned by the didactic-moralistic nature of the text.
Keywords: antonyms; pragmatics; the Biblical discours; hate; love